Pengaruh Variasi Waktu Inkubasi dengan Penambahan Paya Meat Tenderizer pada Proses Dekafeinasi Kopi Arabika (Coffea arabica L.) - DEWA AYU RATIH; MADE SRITAMIN; I GEDE PUTU WIRAWAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
Effect of Incubation Time Variation with The Addition of Paya Meat Tenderizer in the Arabica Coffee Decaffeination Process (Coffea arabica L.) High levels of caffeine lead to insomnia and increased blood pressure. Decaffeination is a solution to reduce the caffeine with enzymatic method with papain coarse extract PAYA Meat Tenderizer contains proteolytic activity of 1,0593 units/g. The study aims to find out the effect of arabica coffee incubation time with the addition of the enzyme papain PAYA Meat Tenderizer. The study looked at protein levels (Kjeldahl), caffeine levels (UV-Vis spectrophotometry) and organoleptic tests. The design used is Complete Random Design (RAL) 4 incubation time treatment i.e. B0 (0 hours); B1 (12 hours); B2 (24 hours) and B3 (36 hours). The results showed a very real influential treatment of all observed variables. B2 (24-hour incubation) lowers caffeine levels by 0,006%. A 0,12% decrease in protein levels occurred in 36-hour incubation. The highest results on organoleptic tests of aroma, viscosity and bitter taste parameters were obtained control samples (B0) and 36-hour (B3).